The protective effects of Aspalathus linearis (Rooibos) extracts against LPS/TNF-α induced inflammation in keratinocytes - Abrahams, Claudia Cathrine (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.